PENGARUH PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS, UKURAN KANTOR AKUNTAN PUBLIK (KAP), AUDIT FEE, DAN OPINI AUDIT TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2019 - Adolpino Nainggolan; Tagor Darius Sidauruk; Eyndah Fajar Cahyani (Jurnal Liabilitas, 2022)
This study aims to analyze the effect of management change, financial distress, size of Public Accounting Firm (KAP), audit fee and audit opinion on auditor switching. The population of this study is all property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The method used to determine the sample is purposive sampling with 90 samples obtained. The data analysis method used logistic regression analysis. The results of the study partially that management change and KAP size have no effect on auditor switching, while financial distress, audit fees, and audit opinions have a significant effect on auditor switching. Simultaneously, the variable of financial distress management turnover, audit fee, and audit opinion has an effect on auditor switching by 29.5% while the remaining 70.5% is influenced by other variables not included in this study. Keywords: Management Change, Financial Distress, Public Accounting Firm Size (KAP), Audit Fee, Audit Opinion, Auditor Switching .